2022
DOI: 10.3390/ijerph19031438
|View full text |Cite
|
Sign up to set email alerts
|

Approaches Used to Describe, Measure, and Analyze Place of Practice in Dentistry, Medical, Nursing, and Allied Health Rural Graduate Workforce Research in Australia: A Systematic Scoping Review

Abstract: Redressing the maldistribution of the health workforce in regional, rural, and remote geographical areas is a global issue and crucial to improving the accessibility of primary health care and specialist services. Geographical classification systems are important as they provide an objective and quantifiable measure of access and can have direct policy relevance, yet they are not always consistently applied in rural health research. It is unclear how research focusing on the graduate health workforce in Austra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 87 publications
(131 reference statements)
1
16
0
Order By: Relevance
“…The application of large artificial boundaries can result in the misidentification of these characteristics [ 131 , 132 ]. Consistent with other research [ 23 ], this review also shows variations in rurality definitions. The lack of a standardised approach further hinders the ability to compare articles and health service access across remoteness areas.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The application of large artificial boundaries can result in the misidentification of these characteristics [ 131 , 132 ]. Consistent with other research [ 23 ], this review also shows variations in rurality definitions. The lack of a standardised approach further hinders the ability to compare articles and health service access across remoteness areas.…”
Section: Discussionsupporting
confidence: 91%
“…A systematic review by Alston et al [ 22 ] on the burden of cardiovascular disease (CVD) in Australia found that some rural and urban areas could not be compared due to the heterogeneity of methods and geographic classifications, consequently, the authors could not provide a clear conclusion on the level of disparity in CVD outcomes by remoteness. Similarly, Beks et al [ 23 ] also reported variations in the use of geographical classification approaches to defining rurality, including systems that are no longer meaningful to policymakers and adaptations of existing systems that make study comparisons difficult.…”
Section: Introductionmentioning
confidence: 99%
“…As in other countries, in Australia, rural or remote areas are classified as according to the government’s classification systems, 12 which are used this to prioritise and incentivise staffing, including allocation of funding for education and training. 13 Such incentives, however, do not generally extend to support for medical imaging practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…In the evidence around mobile clinics, funding has been cited as a challenge due to the reliance on multiple funding sources, including grants from philanthropic organizations [ 1 , 9 ]. The maldistribution of the health workforce is an established issue in rural and remote geographical regions [ 49 ] and is evident in the current study by the challenges encountered to maintaining a GP.…”
Section: Discussionmentioning
confidence: 99%